HUBUNGAN DKP DENGAN KEJADIAN KETUBAN PECAH DINI DI RSUD DR. M. YUNUS BENGKULU - Arsiana, Dian (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Earlier rupture at membrane case has a great contribution to perinatal mortality, one of which is caused by the DKP. Earlier rupture at membrane case at the Dr. M. Yunus hospital Bengkulu increases every year. In 2011, it is recorded Earlier rupture at membrane 482 case (21,5%). The purpose of this study is to recognize DKP correlation with the earlier rupture at membrane case in Dr M. Yunus hospital Bengkulu 2012. This study used case-control design where all in the space C1 maternal Midwifery in 2011 amounted to 2244 people, a sample is taken with a ratio of 1:1 ie 190 by systematic random sampling. The research was conducted in July to August 2012. Retrieval of data using secondary data obtained from maternal registers. Data were analyzed with univariate and bivariate analysis using chi square test. The results showed that a small percentage (3.7%) respondents with DKP, more than most (55.3%) of respondents with parity primiparous and grandemultipara, a small portion (12.6%) of respondents with gestational age preterm and post-mature and small proportion (14.2%) of respondents to the location of the abnormality. There is no significant relationship between the DKP, parity, gestational age, mal position and Earlier rupture at membrane cases. Medical officer, especially midwives, must increase the frequency of counseling about the prevention and treatment for mothers who have risky factors in midwifery polyclinic.